MENINGKATKAN PRESTASI BELAJAR SISTEM PEMERINTAHAN DAERAH DAN STRUKTURNYA BIDANG STUDI PKn DENGAN MENERAPKAN MODEL PEMBELAJARAN KOLABORASI PADA SISWA-SISWI KELAS IV SDN 002 BANGUN PURBA 1 TAHUN PELAJARAN 2015/2016 - ., Amrizal (Universitas Pasir Pengaraian, 2016)
This study uses action research (action research) as much as two rounds. Each round consists of four phases: design, activities and observation, reflection and revision. The target of this study is the class IV SDN 002 Bangun Purba. The data obtained as the result of formative tests, observation sheet teaching and learningactivities. From the analyst found that student achievement increased minimum completeness criteria from the first cycle to the third cycle, namely, the first cycle (9,09%) and cycle II (66,66%). Cycle III 100%. It concluded that the teaching modelof collaboration can be a positive influence on learning achievement of learning class IV SDN 002 Bangun Purba and this model can be used as an alternative learning civics.